Optimizing the Construction of Outcome Measures for Impact Evaluations of Intimate Partner Violence Prevention Interventions - Chatterji, Sangeeta (Journal of interpersonal violence, 2023)
Most impact evaluations of intimate partner violence (IPV) prevention interventions use binary measures of “any” versus “no” physical and/or sexual IPV as their primary outcome measure, missing opportunities to capture nuance. In this study, we reanalyzed secondary data from six randomized controlled trials conducted in low- and middle-income countries—Bandebereho (Rwanda), Becoming One (Uganda), Indashyikirwa (Rwanda), MAISHA CRT01, MAISHA CRT02 (Tanzania), Stepping Stones Creating Futures (South Africa), and Unite for a Better Life (Ethiopia), to assess how different conceptualizations and coding of IPV variables can influence interpretations of the impact of an intervention. We compared the standard outcome measures to new measures that reflect the severity and intensity of violence and whether interventions prevent new cases of IPV or reduce or stop ongoing violence. Results indicate that traditional binary indicators masked some of the more subtle intervention effects, and the use of the new indicators allowed for a better understanding of the impacts of the interventions. Conclusions on whether a program is perceived “to work” are highly influenced by the IPV outcomes that the investigators choose to report, and how they are measured and coded. Lack of attention to outcome choice and measurement could lead to prematurely abandoning strategies useful for violence reduction or missing essential insights into how programs may or may not affect IPV. While these results must be interpreted cautiously, given differences in intervention types, the underlying prevalence of violence, sociodemographic factors, sample sizes, and other contextual differences across the trial sites, they can help us move toward a new approach to reporting multiple outcomes that allow us to unpack the “impact” of an intervention by assessing intervention effect by the severity of violence and type of prevention, whether primary and secondary.